2021
DOI: 10.1007/s00296-021-04838-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of osteoarthritis in lower middle- and low-income countries: a systematic review and meta-analysis

Abstract: Evidence from the Global Burden of Disease studies suggests that osteoarthritis (OA) is a significant cause of disability globally; however, it is less clear how much of this burden exists in low-income and lower middle-income countries. This study aims to determine the prevalence of OA in people living in low-income and lower middle-income countries. Four electronic databases (MEDLINE, EMBASE, CINAHL and Web of Science) were systematically searched from inception to October 2018 for population-based studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…In addition, less-developed countries are ageing at a more rapid rate than more-developed countries, with the highest increase in the burden of MSK disorders being currently reported amongst low- and middle-income countries (LMICs) (Blyth et al 2019 ; Hay et al 2017 ). A review by Yahaya ( 2021 ) showed a high prevalence of OA in LMICs with one in six individuals living with OA. The increase in OA within LMICs may be affected by the health inequalities which affect the health status, access and opportunities of these populations (Yahaya et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, less-developed countries are ageing at a more rapid rate than more-developed countries, with the highest increase in the burden of MSK disorders being currently reported amongst low- and middle-income countries (LMICs) (Blyth et al 2019 ; Hay et al 2017 ). A review by Yahaya ( 2021 ) showed a high prevalence of OA in LMICs with one in six individuals living with OA. The increase in OA within LMICs may be affected by the health inequalities which affect the health status, access and opportunities of these populations (Yahaya et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A review by Yahaya ( 2021 ) showed a high prevalence of OA in LMICs with one in six individuals living with OA. The increase in OA within LMICs may be affected by the health inequalities which affect the health status, access and opportunities of these populations (Yahaya et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is the most prevalent type of arthritis ( 1 ) and a very common long-term disabling chronic condition ( 2 ) characterized by the deterioration of cartilage in the joints ( 3 ). Evidence suggests that OA is the leading cause of disability worldwide with very high personal, social and economic burdens ( 4 ). The prevalence of OA increases with age and is more common in women, people with obesity and those with joint trauma ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have proposed intervention programs to promote fruit and vegetable consumption [ 4 , 5 , 6 ] considering the association of their low consumption with some diseases, pointed out from the beginning of 2000s [ 7 , 8 ]. Most of them are called non-communicable diseases by WHO [ 9 ]: cancers [ 10 , 11 , 12 ], obesity [ 13 ], high blood pressure [ 14 ] and other cardiovascular illnesses [ 15 ], strokes [ 16 ], osteoporosis [ 17 ], osteoarthritis [ 18 ], type 2 diabetes [ 19 ], degenerative diseases [ 20 ], among others. They are known to reduce the risk of cancer, heart disease, and diabetes; to inhibit plasma platelet aggregation, cyclooxygenase activity, and histamine release, as well as to exert antibacterial, antiviral, anti-inflammatory, and anti-allergenic activities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%